Ethics on social networking: A preliminary survey in Thailand - Ramingwong L. (2017)
© Int. J. of GEOMATE. The rapid growth of social networks and their users has been phenomenon. This brings numerous changes in everyday life, both positively and negatively. Ethics have become a major growing challenge in this area. Sensitive issues such as privacy, impersonation and cyberbullying are increasingly causing more damage to the community. This research reviews ethical issues on social networks. It also reports results from a survey on the most anticipated ethical concerns from the viewpoints of undergraduate students from Chiang Mai University, Thailand. Lost of privacy, misinformation and impersonation are anticipated as the worst ethical misconducted.